PERANCANGAN TRACER (OUTGUIDE) UNTUK PENYIMPANAN REKAM MEDIS PERSONAL FOLDER DI PUSKESMAS GONDOKUSUMAN I YOGYAKARTA - , YUNANTO HANDOYO; , Savitri Citra Budi, SKM., MPH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Management of health care facilities responsible for lost, damaged, counterfeit, and / or the use by any person or entity who is not entitled to the medical records (Permenkes No. 269 / MENKES / PER / III / 2008 about ownership, utilization, and responsibility Article 14). Researcher found in Gondokusuman I community health center that the ambulatory care medical record filing still not used tracer (outguide) for medical record out or borrowed. This occurs because of the infrastructure. The absence of tracer in the filing area causing frequent misfile and lost medical record, thus hampering search of medical records. Outguides (or tracers) replace a record that is removed from the files for any purpose. They should be made of strong material, preferably colored. There are various types of outguides available. Some include pockets to store requisition slips and loose reports. Others are cardboard folders, which can also store requisition slips and loose sheets. Others are more sophisticated and expensive. All do the same job